Functional mapping of the cerebellum using the activity-dependent transcription factors - Wong, Simin (2016)
Myocyte enhancer factor 2C (MEF2C) is a transcription factor which upregulates its expression in an activity-dependent manner. Despite its activity-dependent nature and expression in several brain areas, including the cerebellum, Mef2C has not been commonly used as a proxy for neuronal activation. Here, we explore the use of activity-dependent expression of Mef2C as a tool to study the cerebellum. Experimental mice were sacrificed at different time points after being subjected to spatial exploration. Through Immunohistochemistry and chromogenic in situ hybridisation, we show that Mef2C RNA expression appears to peak at 45 min and 120 min while the protein expression peaks at 60 min. The RNA expression seems to diminish after 150 min while the protein expression decreases at 90 min. Upon stimulation, we observed an increase in Mef2C expression in all neuronal subtypes in the cerebellum. In addition, Mef2C expression seems to be inversely correlated with c-fos expression. Together, this study shows that Mef2C has the potential to become a neuronal activation marker and could be used to map the activity of the cerebellum and other regions of the brain which express this gene.